Faktor- Faktor yang Berhubungan dengan Kelengkapan Pemberian Imunisasi Dasar pada Anak - Wilda Arafianti; Tisnawati Tisnawati; Wira Heppy Nidia; Zolla Amely Ilda; Suhaimi Suhaimi (Jurnal Sehat Mandiri, 2025)
The cases of vaccine-preventable diseases (PD3I) in Padang City in 2023 were 21 cases of acute flaccid paralysis (AFP), 133 cases of measles, and 5 suspected cases of diphtheria. Family involvement is essential for ensuring children receive complete immunization, including knowledge, attitude, and family support. The aim of this study is to identify factors associated with the completeness of basic immunization administration in children in the Dadok Tunggul Hitam Village Work Area. The study design is an observational analytical cross-sectional study. Data collection took place from August 2024 to June 2025. The study population consisted of 194 mothers with children aged ≥15 months to 24 months, with a sample size of 63 using cluster random sampling. Data collection was conducted using questionnaires and document review, with data processing involving editing, coding, entry, cleaning, and tabulation. Analysis was conducted using the Chi-square test (CI 95%). The results showed a significant association between mothers' knowledge (p-value = 0.000) and family support (p-value = 0.027) with the completeness of basic immunization in children, and no association between mothers' attitudes (p-value = 0.140) with the completeness of basic immunization. It is recommended that health education and outreach activities be conducted in a systematic, comprehensive, and sustainable manner to improve public knowledge about basic immunization for children. These efforts can be carried out in collaboration with health promotion officers at the Dadok Tunggul Hitam Community Health Center through regular and scheduled health education.